The survival probability of shafts and shaft-hub connections. (September 2019) - Vetter, Sebastian; Leidich, Erhard; Neikes, Kai; Schlecht, Berthold; Hasse, Alexander
Abstract: The fatigue limits of shafts and shaft-hub connections are subject to a probability distribution. This distribution can be described by the mean value and the scatter of the fatigue limit. The mean fatigue limit can be determined with very few samples, whereas the scatter cannot be determined precisely. In order to develop a reliable design of shafts and shaft-hub connections, it is certainly necessary to know the scatter of the fatigue limit. Parameters that may influence the scatter are investigated on the basis of evaluated test series from literature, for shafts with failure at the free surface and shaft-hub connections. The analysis focuses on the type of load, the highly stressed surface or the shaft-hub connection type. A calculation method for determining the fatigue limit for a given survival probability will be presented. Highlights: Weighted scatter method to determine the scatter of fatigue limit for test blocks Shafts have a lower scatter of fatigue limit than shaft-hub connections. Type of shaft-hub connection has influence on the scatter of fatigue limit. Method for calculating fatigue limit values for given survival probabilities